2020
DOI: 10.1016/j.foodchem.2020.126389
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biosynthesis of the natural antimicrobial glyceollins in soybean seedlings by priming and elicitation

Abstract: Priming prior to Rhizopus-elicitation enhances the production of glyceollins.• Priming with reactive oxygen species was superior to wounding in glyceollin production.• Reactive oxygen species effectively primed glyceollin production in two cultivars.• Priming prior to Rhizopus-elicitation was specific in inducing glyceollins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
1
3
0
2
Order By: Relevance
“…Among these, the suppression of the recurrence of breast cancer using intact absorbable glyceollin I , was a novel finding only for glyceollins. It is well known that plants may produce phytoalexins in the body as a defense mechanism in response to environmental stresses, such as bacteria, fungi, insects, and light. ,, Aisyah et al also reported that the combined elicitation of the fungus R. oryzae and light stress to soybean promoted the effective production of prenylated isoflavones, including glyceollins; this is similar to the present A.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Among these, the suppression of the recurrence of breast cancer using intact absorbable glyceollin I , was a novel finding only for glyceollins. It is well known that plants may produce phytoalexins in the body as a defense mechanism in response to environmental stresses, such as bacteria, fungi, insects, and light. ,, Aisyah et al also reported that the combined elicitation of the fungus R. oryzae and light stress to soybean promoted the effective production of prenylated isoflavones, including glyceollins; this is similar to the present A.…”
Section: Discussionsupporting
confidence: 79%
“…have diverse isoflavones, including daidzin, genistin, glycitin, and their aglycones . It has been reported that soybeans can also produce a variety of phytoalexins from isoflavones in response to environmental or microbial stresses, , such as coumestrol, C -methyl or 4-prenyl coumestrol, isotrifoliol, glycinol, glyceocarpin, glyceollidins, glyceollins, and glyceofurans, by enzymatic hydroxylation and prenylation reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…This is explained by the fact that, upon pathogen infection, pre-existing phytoanticipin flavonoids can be transformed into active phytoalexins [161,162]. Some exemplary cases are daidzein, a soy phytoanticipin that, once elicited by pathogenic microbes, is transformed by prenylation into glyceollin pterocarpans [163]. Similarly, the active aglycone form of maackiain is obtained by hydrolysis of the conjugated compound and released by infected red clover plants [164].…”
Section: Flavonoids As Weapons Against Phytopathogenic Attacksmentioning
confidence: 99%
“…Otros autores lograron aumentar hasta 4 veces más la producción de gliceollinas una clase de pterocarpanos prenilados antimicrobianos producidos en plántulas in vitro de soja tras la elicitación con una suspensión de esporas de hogos tipo Rhizopus (Kalli et al, 2020).…”
Section: Elicitaciónunclassified
“…Una estrategia que ha demostrado ser efectiva es el uso de elicitores bióticos, por ejemplo, algunas investigaciones que se han llevado a cabo aumentaron la síntesis de psoraleno en cultivos celulares de Psoralea corylifolia de 16 días (Ahmed & Baig, 2014). Otros autores lograron aumentar hasta 4 veces más la producción de gluceollinas una clase de pterocarpanos prenilados antimicrobianos producidos en plántulas in vitro de soja tras la elicitación con una mezcla de hongos de tipo Rhizopus (Kalli et al, 2020).…”
Section: Introductionunclassified